Total Institutions and Stigmatizations - Kron, Leposava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2008)
This paper deals with total institutions in general, mental hospitals in particular and about career of mental patients. The author also referred to Szasz's main arguments that one should be deprived of liberty unless one is found guilty of a criminal offence. Depriving a person of liberty for what is said to be his own good is immoral. Just as a person suffering from terminal cancer may refuse treatment, so should a person be able to refuse psychiatric treatment. Szasz's contention that mental illness is a "myth" appears to rely on a variant of the dualistic Cartesian model of mind versus body. Although the specific social categories that become stigmatised can vary across times and places, the two basic forms of stigma (physical deformity and mental problems) are found in most cultures and time periods, leading some psychologists to hypothesise that the tendency to stigmatise may have evolutionary roots.